MARKETPLACE BERBASISKAN WEB UNTUK KOMUNITAS HIDUP SEHAT - Cuk Tho (Program Studi Teknologi Informasi, 2019)
The improvement of information technology has significant impact in human life including changing the life style. As one of the improvements is the development of web-based market place. People can purchase something without physically coming to the market by accessing the web-based market place. This paper presents the marketplace for diet community which connecting people that adopting healthy lifestyle with catering and nutritionist. Consultation can be made online, and recommendation can be directly sent to catering to provide healthy daily food. Laravel and Scrum approach are used in developing this web-based marketplace. This web base market place has received good responses from several customers, nutritionist and diet catering, However, further development is still needed to improve the performance of this marketplace